1986
DOI: 10.1002/jcp.1041290308
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between plasma membrane surface area and transferrin secretion rate in isolated hepatocytes

Abstract: It is generally considered that in exocytosis the size of the secreting cells does not increase when the membranes of exocytosis vesicles fuse with the plasma membrane. As the factors involved in the regulation of this phenomenon are poorly understood, we thought it worthwhile to investigate the relationship between the plasma membrane surface area and secretory activity. Isolated rat hepatocytes were prepared by liver collagenase perfusion. Secretion of the plasma protein, transferrin (Tf) was detected at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…At the present time, the tech nique has been used only to study plasma protein secretion by a global population of isolated hepatocytes and not by hepatocytes isolated from a particular lobular zone. We have demonstrated that the rate of secretion for several plasma proteins, such as albumin [112,113], fibrinogen [113] or transferrin [114], varies from hepatocyte to hepatocyte and increased with the cell size [112,114]. It is difficult to transpose these results in vivo since the size of individual hepatocytes has not been measured in situ.…”
Section: Hepatocellular Heterogeneity For Plasma Protein Synthesismentioning
confidence: 97%
“…At the present time, the tech nique has been used only to study plasma protein secretion by a global population of isolated hepatocytes and not by hepatocytes isolated from a particular lobular zone. We have demonstrated that the rate of secretion for several plasma proteins, such as albumin [112,113], fibrinogen [113] or transferrin [114], varies from hepatocyte to hepatocyte and increased with the cell size [112,114]. It is difficult to transpose these results in vivo since the size of individual hepatocytes has not been measured in situ.…”
Section: Hepatocellular Heterogeneity For Plasma Protein Synthesismentioning
confidence: 97%
“…Even though this determination did not include the change in microvilli surface area or membrane blebbing observed, the results 55 suggest that membrane area may not be a ratedetermining factor in hybridoma respiratory metabolism (Clegg and Gordon, 1985) or Ig secretion. This is in contrast to the correlation between plasma membrane surface area and transferrin secretion rate in isolated hepatocytes (Pechinot et al, 1986) and recent implications that the degree of hybridoma microvilli density may be related to MoAb secretion (Kitano et al, 1988).…”
Section: Discussionmentioning
confidence: 56%
“…As cell volume changes, surface membrane area, membrane recycling (Novak et al, 1988) and the distribution of blebs and microvilli may also change. Membrane blebbing and the density of microvilli may be related to available reserve surface membrane for rapid nonmetabolic expansion of cell volume (Erickson and Trinkaus, 1976;Borrelli et al, 1986;Clegg, 1986), nutrient uptake and protein secretion rate in constitutively secreting cells (Pechinot et al, 1986). Hybridoma morphology is intimately related to cell cytoskeletal filaments and subcellular organelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferrin (Tf), like most other plasma proteins, is synthesized by hepatocytes [12,25,37] and its production in normal and/or pathological states has been extensively investigated [6,15,26,30,33]. We previously demonstrated at the single cell level that the amount of secreted Tf is proportional to the size of secreting hepatocytes and constant per unit plasma membrane surface area and per unit time [31]. The aim of the present work was to establish whether a relationship exists or not between Tf secretion and hepatocytic ploidy.…”
Section: Introductionmentioning
confidence: 99%